Bibliometric analysis of burnout and optimism in sport - Marín, E.; Ortín, F. J.; Garcés de los Fayos E. J.; Tutte, V. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
Bibliometric studies are of paramount importance in the context of the evaluation of scientific content. At the same time, are useful in allowing a detailed approach and analyzed the data provided on a particular subject area. This study presents a review of published scientific work, until 2011, and optimism on burnout in sports to know the status of the issue of these variables. The search was performed through electronic databases, PsycINFO and SCOPUS. After selecting the documents, information obtained through reading was collected in a matrix creating a database that included relevant data. Finally, we analyzed the most relevant information: number of published articles, authors involved in each of the work, geographical distribution, research, publication type, journals, methods, variables and instruments used. The study results confirm the increase of works about burnout and optimism as constructs within psychology research in physical activity and sport.